Ultrastructural Characterization of Corticotropin-Releasing Factor and Neuropeptide Y in the Rat Locus Coeruleus: Anatomical Evidence for Putative Interactions. (1st August 2018) - Theisen, Catherine C.; Reyes, Beverly A.S.; Sabban, E.L.; Van Bockstaele, Elisabeth J.
Highlights: NPY and CRF were co-localized within the same axon terminals in the LC. CRF-labeled axon terminals directly contacted Y1R-labeled dendrites in the LC. CRF-labeled axon terminals also contained Y2R in the LC. Findings indicate multiple anatomical interactions between CRF and NPY in the LC. Abstract: As a neurochemical mediator of stress resilience, NPY has been shown to oppose excitatory effects of the pro-stress neuropeptide corticotropin-releasing factor (CRF). Previous studies have described the anatomical organization of NPY and CRF in the central nucleus of the amygdala, which sends CRF projections to the locus coeruleus (LC), activating LC norepinephrine release. However, the cellular substrates for interactions between NPY and CRF in the LC remain unknown. In this study, we investigated these anatomical substrates in the male rat LC, using immunocytochemistry, confocal microscopy, and immunoelectron microscopy to detect NPY and CRF, as well as CRF and Y1 or Y2 receptors (Y1R or Y2R). Immunofluorescence and electron microscopy revealed both co-localization of NPY and CRF in LC axon terminals, as well as separately labeled terminals, suggesting NPY and CRF may serve as co-transmitters in a subset of terminals. Semi-quantitative analysis showed that 32.4% of CRF-labeled terminals contained NPY, while 58.2% (152/261) of NPY-labeled terminals contained CRF. With respect to Y1R and CRF, dual immunoelectron microscopy showed that 23.3% (67/288) of CRF-labeled axon terminals directly contacted Y1R-labeled dendrites, while only 6.3% (18/288) of CRF-labeled axon terminals co-localized with Y1R. Dual immunoelectron microscopy also showed Y2R co-localized with 30.4% (103/339) CRF-labeled terminals, but only with 16.2% (55/339) of dendrites post-synaptic to CRF-labeled axon terminals in the LC. Taken together, these findings indicate multiple sites of interaction between CRF and NPY in the LC and suggest that conditions or drugs that modulate the NPY:CRF balance in the LC may promote stress resilience.